Thirty years after the Berlin Wall: german unification and transformation research - Heller, Ayline; Schmidt, Peter (Routledge advances in sociology, 2024)
This book examines the increasing body of research dedicated to the lasting differences between the former separate states of the Federal German Republic (FRG) and the German Democratic Republic (GDR). Thirty years after the fall of the Berlin Wall, it takes a broad view on German unification and transformation research.